"My voices are just part of me, they don't own me": a qualitative investigation of Acceptance and Commitment Therapy groups for people experiencing psychosis. Issue 3 (3rd July 2021) - Bloy, Sally; Morris, Eric M.J.; Johns, Louise C.; Cooke, Anne; Oliver, Joseph E.
ABSTRACT: Background : This study aimed to generate a grounded theory of change processes as experienced by people with psychosis who engaged in an Acceptance and Commitment Therapy (ACT) group program. A secondary aim was to identify how participants described changes in their relationship to distress following the groups. Methods : The study used a qualitative research methodology, grounded theory. This was used to explore emergent themes in the participants' subjective experiences of group ACT delivered in community mental health services. The experience of the ACT group process was investigated for nine participants. Semi-structured interviews were used to explore how the group experience and the exercises, metaphors and skills promoted by ACT were used by participants in their daily lives. Results : There were four main themes emerging from the interviews: awareness, relating differently, reconnection with life, leaning on others. Conclusions : The participants all described experiencing subjective benefits from being involved in the ACT groups, along with perspectives on processes of change. These reports of changes were consistent with the model and extend our understanding of the lived experience of engaging in ACT for psychosis groups.